ASSESSMENT OF CRITICAL SUCCESS FACTORS FOR EFFECTIVE SUPPLIERS’ SELECTION: ASSESSING THE DIMENSION, THEORY AND EFFECT OF ETHICS CULTURE TOWARDS SUPPLIER PERFORMANCE - Amuzat, Olawale; ENO, Ndifreke Akaninyene (PT. Altin Riset Publishing, 2024)
This research aims to assess the Critical Success Factors (CSFs) for effective supplier selection, focusing on the dimensions, theory, and impact of ethical culture on supplier performance. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive data from public and private sector companies. Key factors evaluated include quality, price, technical capability, ethical culture, performance history, and reputation. The quantitative data reveals that quality is the primary criterion, followed by competitive pricing and technical capabilities. Ethical culture is highlighted as a significant influence on supplier performance, affecting trust and long-term relationships. Qualitative insights emphasize the positive experiences companies have with ethical suppliers and the challenges in assessing ethical culture. The findings are discussed about value co-creation theory, which underscores the collaborative creation of mutual value between companies and suppliers, and agency theory, which addresses the principal-agent relationship and potential conflicts of interest. Practical implications suggest that companies should incorporate ethical culture assessments into their supplier selection processes and focus on building long-term relationships with reputable suppliers. This approach can enhance operational efficiency, trust, and overall performance. The study concludes that integrating these critical factors into supplier selection can significantly improve the strategic outcomes and competitiveness of companies.